A Thematic Analysis of N.G. Sibiya’s Selected Essays in Amalangabi - Sizwe Zwelakhe Dlamini (The Thinker)
The aim of this paper is to critically examine themes that are found in N.G. Sibiya’s selected essays in Amalangabi (1993). It was discovered that Sibiya highlights some thought-provoking issues in his essays, but to the best of the researcher’s knowledge, nothing or less has been done so far about Sibiya’s work on the essay genre. It is this scholarly gap that this study is attempting to fill. The study is done through the post-colonial approach since the selected themes touch on social aspects. The themes ‘Discrimination against people with stutters’, ‘Stereotypes against people with stutters’, and ‘Patience produces good results’ are examined from the essays ‘Amalimi’ and ‘Ukulinda’.